THE EFFECT OF PERSONAL FINANCIAL MANAGEMENT, ATTITUDE TOWARDS DEBT, AND BANKING KNOWLEDGE ON FINANCIAL COMPLIANCE THROUGH MEDIATION OF SELF-CONFIDENCE - Wiyanti S, Lina; Suhardi, Suhardi; Firdaus, Rahmad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyse the role of confidence in financial management as a mediator between personal finance management, banking knowledge, attitude towards debt, and financial compliance among Indonesian adults. The research method used was a quantitative survey with a cross-sectional approach, involving 170 respondents selected by purposive sampling. Data were collected through an online questionnaire and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). The results showed that confidence in financial management significantly mediated the relationship between personal financial management and financial compliance, but no significant mediating effect was found on the banking knowledge pathway. A positive attitude towards debt also showed a marginal mediating effect through self-confidence. These findings emphasise the importance of financial education interventions that focus not only on the knowledge aspect but also on strengthening confidence and positive attitudes in financial management.